Go home, cat! - Redfern, Cameron S. 1968- (Puffin Books, 2022)
A delightful story from the award-winning team who brought us Come Down, Cat! that celebrates friendship, courage and the value of those we love. When Nicholas finds a silver coin in the garden, he tells his cat, 'I can buy liquorice with this!' Nicholas loves liquorice more than almost anything. 'Stay home, cat, ' he says, and sets out for the shop. But as Nicholas walks down the street he hears a voice he knows ...